2015
DOI: 10.1111/ddi.12300
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐driven changes in winter abundance of a migratory waterbird in relation to EU protected areas

Abstract: Aim Species are responding to climate change by changing their distributions, creating debate about the effectiveness of existing networks of protected areas. As a contribution to this debate, we assess whether regional winter abundances and distribution of the Smew Mergellus albellus, a migratory waterbird species listed on Annex I (EU Birds Directive) that overwinters exclusively in European wetlands, changed during 1990–2011, the role of global warming in driving distributional changes and the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 25 publications
(66 reference statements)
4
94
0
3
Order By: Relevance
“…As a consequence, changes in species distributions could lead to increases in species richness and numbers in locations at the edge of what might have been previously considered to be 'normal' wintering areas Pavón-Jordán et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a consequence, changes in species distributions could lead to increases in species richness and numbers in locations at the edge of what might have been previously considered to be 'normal' wintering areas Pavón-Jordán et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Despite both increasing and decreasing trends in wintering waterbird population sizes in the Western Palearctic (Wetlands International 2006, previous studies have consistently shown a prevailing increase in the numbers of most waterbird species in Central Europe (Fox et al 2010;Keller 2011;Musil et al 2011;Slabeyová et al 2014), most likely due to the results of large-scale changes in the climate (Ridgill and Fox 1990;Maclean et al 2008;Lehikoinen et al 2013;Pavón-Jordán et al 2015). Moreover, the higher levels of eutrophication of European wetlands in the 20th century (Vollenweider 1968) may have led to increases in the trophic levels of wetlands and, consequently, increases in wintering waterbird numbers, as has been shown in Switzerland (Suter and Schifferli 1988).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations